PAI TEACHER PROFESSIONALISM IN RESPONDING TO TECHNOLOGY TO INCREASE STUDENT LEARNING MOTIVATION - Zuliana Zuliana; Mutiara Ummi; Cahya Golbin Aisaroh (Proceeding International Seminar of Islamic Studies, 2023)
This study aims to explore the difficulties faced by Islamic Religious Education (PAI) teachers in responding to technology in the digitalization era. The method used in this study is a qualitative method with a descriptive analysis approach where the research focuses on collecting data based on the experience of the subjects studied (PAI teachers). The survey stated that the response of PAI teachers to the touch of technology to increase students' motivation in learning was determined by three respondents: (1) accepting technological advances wisely and taking positive impacts, (2) rejecting and not accepting change for fear of not being able to filter out negative impacts, and (3) hesitant because of the teacher's lack of knowledge of the positive and negative impacts of technology. The use of information technology by mankind, including Islamic religious education teachers, must be based on religious norms, which are used as guidelines for doing good and positive activities, such as being able to take advantage of available sources, media, methods, and learning tools. A professional teacher will be responsible for accepting technological advances wisely and taking positives from technological advances. Teachers as learning agents must be supported by the availability of technological facilities both from the government, institutions, and individuals, as well as knowledge and skills in using technological tools and resources. Thus, teacher professionalism can be accounted for along with increased student motivation in learning. Keywords: Teacher, Professionalism, Technology, and Information